Use of Functional Magnetic Resonance Imaging to Assess How Motor Phenotypes of Parkinson's Disease Respond to Deep Brain Stimulation. (1st September 2019) - DiMarzio, Marisa D; Madhavan, Radhika; Joel, Suresh; Hancu, Ileana; Fiveland, Eric; Prusik, Julia; Gillogly, Michael; Rashid, Tanweer; Ashe, Jeffrey; Telkes, Ilknur; Feustel, Paul; Shin, Damian; et al.
Abstract: INTRODUCTION: Deep brain stimulation (DBS) is a well-accepted treatment of Parkinson's disease (PD). Motor phenotypes include tremor-dominant (TD), akinesia-rigidity (AR), and postural instability gait disorder (PIGD). The mechanism of action in how DBS modulates symptom relief remains unknown. METHODS: Subjects who were classified into TD, AR, or PIGD cohorts underwent task-based fMRI. The effects of the task [DBS (ON/OFF)] on BOLD activation in each phenotype were documented through general linear voxel-wise analysis. For group analysis, t -values were compared using ANOVA in regions of interest, including the primary motor cortex (MI), motor thalamus, primary somatosensory cortex (SI), globus pallidum externus (GPe), anterior and posterior cerebella, supplementary motor area (SMA), and caudate and putamen. A 2-way ANOVA analysis was performed to assess the impact of age, phenotype, and target nuclei. RESULTS: BOLD activation with DBS-ON compared to the OFF state resulted in activation in the motor thalamus ( P  < .01) and GPe ( P  < .01) when analyzed as a group. Among phenotype, age of PD onset, and target nuclei, phenotype was most effective in determining activation levels. Specifically, AR patients had more activation in the SMA than PIGD patients ( P  = .002) and in MI compared to TD and PIGD subjects ( P  = .001 and P  = .017, respectively). Further analysis demonstrated that the implant brain region affected activation patterns only in PIGD patients. Specifically, globus pallidum internus (GPi) DBS resulted in MI and SMA deactivation, while STN DBS led to MI activation with no changes in the SMA. CONCLUSION: These data suggest that DBS modulates network activity differently based on patient motor phenotype. The nuclei where DBS is implanted affected activation patterns in the PIGD cohort. An improved understanding of these differences may allow us to further our knowledge about the mechanisms of DBS action on PD motor symptoms and to exploit connections to optimize treatment.